Understanding Sleep Disturbances in ADHD: Neurobiology, Circadian Mechanisms, and Clinical Impact - Piegza, Natalia; Domańska, Karolina; Makowska, Joanna; Darmoń, Jerzy; Windyga, Maria; Sieczka, Anna; Papuga, Aleksandra; Hejduk, Makary (Quality in Sport, 2026)
Background: Sleep disturbances are common in adults with attention-deficit/hyperactivity disorder (ADHD) and often include problems such as insomnia and circadian rhythm disturbances, which may negatively affect cognitive functioning and daily performance. However, their clinical characteristics and underlying mechanisms in adult ADHD remain incompletely understood. Aim: This narrative review synthesizes current evidence on sleep disturbances in adults with ADHD, focusing on prevalence, clinical characteristics, types of sleep disorders, mechanisms, and clinical implications. Materials and Methods: ​​This narrative review was based on the analysis of published scientific literature retrieved from online databases related to attention-deficit/hyperactivity disorder (ADHD) and sleep. Relevant publications were selected based on their relevance to the topic, with a focus on studies involving adult populations. Most of the included studies were published between 2015 and 2026, with earlier key publications included for background context. Various types of studies were considered, including reviews, clinical studies, and theoretical papers. The findings were synthesized qualitatively. Results: Approximately 60% of adults with ADHD screen positive for sleep disorders, primarily insomnia and delayed sleep–wake phase disorder. Underlying mechanisms are multifactorial, involving circadian dysregulation, neurobiological, and behavioral factors. These issues are also associated with psychiatric comorbidities and impairments in executive functioning. Conclusions: Sleep disturbances represent a clinically relevant aspect of adult ADHD. Their heterogeneity and complex mechanisms should be considered in clinical practice. Further research is needed to clarify their characteristics and the role of sleep-focused interventions.